Species-specific effects of microplastics on juvenile fishes - Zhang, Chaonan; Wang, Fei; Wang, Qiujie; Zou, Jixing; Zhu, Junjie (Frontiers in Physiology, 2023)
Microplastics contamination have been extensively reported in aquatic ecosystem and organisms. It is wildly acknowledged that the ingestion, accumulation and elimination of microplastics in fishes are species-specific, which mainly depending on the feeding behavior. This study aimed to investigate the effects of microplastics on the morphology and inflammatory response in intestines of fishes with different feeding types. Largemouth bass (carnivorous fish), grass carp (herbivorous fish) and Jian carp (omnivorous fish) were used as organism model. The contributing concentration and size of microplastics were explored as well as the response time and legacy effect in fishes. Two different sizes of polystyrene microplastics (80 nm and 8 μm) were set at three concentrations. And samples were analyzed at different exposure times and depuration times. Histological analysis indicated that multiple abnormalities in intestines were presented in three species fishes after acute exposure microplastics. The mRNA abundance of immune-related genes in the intestine tissues of fishes were significantly fluctuant. There were differential expressions of genes coping with differential sizes and concentrations of microplastics exposure in different fishes. The reason for the difference effects of microplastics on fishes was still unclear but could be due to the difference in the structure and function of the digestive system. These results provided a theoretical basis to further analysis of the mechanism of fish intestinal pathology caused by microplastics.